Clergy and Funeral Directors: An Exploration in Role Conflict - Bradfield, Cecil D. (Review of religious research, 1980)
Clergy and funeral directors are required to work together in the death setting. This article explores the nature of their relationship and areas of role conflict. A questionnaire was sent nationwide to 275 Lutheran clergy. The respondents were asked to relate their perceptions of, and relationships with, funeral directors. The results of the investigation suggest that role conflict has lessened as funeral directors have become more "professionalized" and clergy have tended to be more accepting of that new status. The issue of "Who is in charge?" of the funeral is of critical importance in the amount of conflict in a specific situation. Many of the respondents believed that the conflict which does exist could be alleviated if clergy and funeral directors made a greater effort to understand one another's roles.